The Value Premium on the Danish Stock Market: 1950-2004 - Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2005)
A number of influential studies have documented a strong value premium for US stocks over the period 1963 to 1990 (Fama and French (1992), Lakonishok et al. (1994)). Stocks with low price-earnings multiples, price-book values and other measures of value are reported to have given a higher mean return than the high multiple growth firms. Work by Basu (1997) and others have shown that the value dominance is also a feature of the earlier market history of the United States. The value premium is reported also to exist in a number of other countries over the period 1975 to 1995 (Fama and French (1998)). The results for these markets are based on Morgan Stanley (MSCI) data. Since these data are softer due to a relatively short time horizon and due to a small number of stocks in some cases down at 10 stocks, the conclusions are likely to be less robust. There is therefore a need for more research on this issue. The purpose of this paper is to report evidence for the Danish stock market and to test whether the value premium is a genuine long-term feature of the market or just a phenomenon that pops up now and then. To research this issue we have collected accounting and stock market data for more than half a century. We report in particular on the insights obtained when portfolios are formed on the basis of the price-earnings multiple. The paper shows that there is a value premium. The paper also analyzes whether the premium is likely to be due to risk (Fama and French (1992,98)) or mispricing as emphasized by the Behavioral Finance School (Chan et al. (2000), Lakonishok et al. (1994) and La Porta et al. (1997)).
hdl:10398/7613
Keywords: H00; 330; Stock market